Doing Statistics for Business with Excel: Data, Inference, and Decision Making - Pelosi, Marilyn K.; Sandifer, Theresa M. (Wiley, 2002)
Keywords: Commercial statistics; Statistics; Industrial management; Statistical methods; dept.mat; faculty_collection

Color spreading algorithm for the retail industry - Pelosi, Marilyn K; Sandifer, Theresa M; Sandifer, C Edward (Annual Conference on Computers, 1992)
One of the problems which many companies face is the distribution of inventory from one or more centrally located distribution centers. The retail, industry, and in particular the women's clothing industry, faces the additional problem that not only does the merchandise have to be distributed but it must be distributed in such a way that every store gets a reasonable spread of colors and sizes. This research attempts to optimize the multi-criteria allocation objective by developing a computer algorithm. In order to be implemented any algorithm developed must be computationally efficient due to the size of the industry and other system related programming constraints. The algorithm which was developed not only provided a solution which was a marked improvement regarding the color spread of the merchandise but was also efficient enough to be immediately implemented on a national basis. © 1992.
0 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Algorithms; Garment manufacture; Multi-criteria allocation objective; Retail industry color spreading algorithm; Retail stores; Women's clothing industry; dept.mat